Elevated IL-17 levels in semi-immune anaemic mice infected with Plasmodium berghei ANKA - Gideon Kofi Helegbe; Nguyen Tien Huy; Tetsuo Yanagi; Mohammed Nasir Shuaibu; Mihoko Kikuchi; Mahamoud Sama Cherif; Kenji Hirayama (Malaria Journal, 2018)
Abstract Background Alterations in inflammatory cytokines and genetic background of the host contribute to the outcome of malaria infection. Despite the promising protective role of IL-17 in infections, little attention is given to further understand its importance in the pathogenesis of severe malaria anaemia in chronic/endemic situations. The objective of this study, therefore, was to evaluate IL-17 levels in anaemic condition and its association with host genetic factors. Methods Two mice strains (Balb/c and CBA) were crossed to get the F1 progeny, and were (F1, Balb/c, CBA) taken through 6 cycles of Plasmodium berghei (ANKA strain) infection and chloroquine/pyrimethamine treatment to generate semi-immune status. Cytokine levels and kinetics of antibody production, CD4+CD25+T regulatory cells were evaluated by bead-based multiplex assay kit, ELISA and FACs, respectively. Results High survival with high Hb loss at significantly low parasitaemia was observed in Balb/c and F1. Furthermore, IgG levels were two times higher in Balb/c, F1 than CBA. While CD4+CD25+ Treg cells were lower in CBA; IL-4, IFN-γ, IL-12α and IL-17 were significantly higher (p < 0.05) in Balb/c, F1. Conclusions In conclusion, elevated IL-17 levels together with high IL-4, IL-12α and IFN-γ levels may be a marker of protection, and the mechanism may be controlled by host factor (s). Further studies of F2 between the F1 and Balb/c will be informative in evaluating if these genes are segregated or further apart.